2001
DOI: 10.1038/sj.bmt.1703162
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation of multiplex fluorescent short tandem repeat analysis for chimerism testing

Abstract: Summary:To evaluate the origin of cells after allogeneic haematopoietic stem cell transplantation we optimised and evaluated two commercially available systems (AmpFlSTR Profiler Plus and GenePrint Powerplex-16) which are based on multiplex fluorescent short tandem repeat (STR) analysis. A standard procedure for interpretation of electropherographs was found essential to obtain reproducible results. On the basis of the relative length of donor and recipient alleles, TYPE-I (no shared alleles are used to calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 13 publications
0
83
0
1
Order By: Relevance
“…DNA extraction and sequencing in both parents revealed no mutation in CASR gene, and as molecular analysis using microsatellite markers (24) indicated that the paternity was as stated, a diagnosis of a de novo heterozygous CASR mutation was made. Figure 1 Clinical case 1.…”
Section: Casementioning
confidence: 99%
“…DNA extraction and sequencing in both parents revealed no mutation in CASR gene, and as molecular analysis using microsatellite markers (24) indicated that the paternity was as stated, a diagnosis of a de novo heterozygous CASR mutation was made. Figure 1 Clinical case 1.…”
Section: Casementioning
confidence: 99%
“…Stutter bands are additional peaks, 2-6 base pairs shorter than the target allele and result from "slippery" amplification by the Taq polymerase during PCR (Nollet et al, 2001;Schraml and Lion, 2003). In the case of dinucleotide repeat loci, the most prevalent stutter band is generally two bases shorter than the main allele band.…”
Section: Discussionmentioning
confidence: 99%
“…Probably this short stutter band simply lacks one core repeat unit relative to the main band (Walsh et al, 1996). The amount of stutter bands produced is proportional to the amount of original allele and range between 0.5-13% (Nollet et al, 2001). However, the stutter band interference is highly variable among different markers and should be used as an important criterion to exclude a marker for this kind of assay.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood samples were collected from the donor and recipient before SCT to establish a pre-transplant STR profile for each donor-recipient pair. These profiles were applied in the post-transplant period when donor chimerism was calculated as described by Nollet et al 6 The recipient was considered to achieve complete donor chimerism if 100% of peripheral blood or bone marrow cells were of donor origin.…”
Section: Hematologic Recovery and Engraftmentmentioning
confidence: 99%